Þróun á meðferð og kostnaði góðkynja stækkunar hvekks á Íslandi - Sigmar Jack; Guðmundur Geirsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2008)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: During the last eight years there has been a dramatic change in the treatment of patients with benign prostatic hyperplasia (BPH) in Iceland. The number of transurethral resection of the prostate (TURP) has decreased while at the same time there has been a growing tendency to treat patients with a1-blockers and finasteride. The purpose of this study was to obtain statistical information regarding these changes and to estimate alterations in the cost of the BPH treatment. Possible changes in indications for TURP were also looked at. Material and methods: Information on the number of patients who underwent surgery since 1984 was gathered from Icelandic hospitals. Information on the use and cost of medical treatment was obtained from the Icelandic Social Security. Medical records of 587 men who underwent surgery in the years 1988-1989 and 1998-1999 were reviewed. Results: Since 1992 the number of TURP operations per year has dropped from its peak of about 560 to around 270 in 1999. This is more than a 50% reduction in eight years. The number of patients being treated for BPH has multiplied since the introduction of drugs and the total cost of BPH treatment has doubled since 1984. There was a trend but not a significant change in indications for TURP when the two periods were compared. Conclusions: Increasing number of Icelandic men with BPH are now recieving treatment although the number of TURP operations has decreased. The total cost of treatment has doubled since 1984, mainly attributed to the advent of medical treatment. Inngangur: Á síðasta ártaugi hefur brottnámsaðgerðum á hvekk um þvagrás (transurethral resection of the prostate, TURP) fækkað verulega, á sama tíma og meðferð með lyfjum af gerð a1-viðtækjablokkara og 5-a redúktasablokkara, hefur aukist mikið við meðferð góðkynja hvekksstækkunar (benign prostatic hyperplasia, BPH). Markmið rannsóknarinnar var að taka saman tíðnitölur og meta kostnað ...